A Study on the Effectiveness of the Independent Director System on the Governance of Financial Fraud Phenomenon: Taking Kangmei Pharmaceutical as an Example - Xu Yang (SHS Web of Conferences, 2024)
This paper explores the pervasive challenge of financial fraud in listed companies, emphasizing the vital role of the independent director system in corporate governance and fraud prevention. Beginning with a background overview and theoretical foundation, it assesses the status and significance of independent directors, analyzing factors influencing their involvement in preventing financial fraud. Using Kangmei Pharmaceuticals as a case study, the paper examines the corporate financial fraud methods and relevant risks, focusing on internal governance issues. Emphasis is placed on the independence of independent directors, their relationships with the board and supervisory board, and their impact on Kangmei Pharmaceuticals’ governance in the financial fraud context. The study uncovers reasons for perceived failures, concluding with recommendations to enhance independent directors’ engagement in corporate governance. This research contributes to understanding financial fraud governance mechanisms, enriching the theory of independent directors, and proposing suggestions to improve the effectiveness of the independent director system.